Морфометрические показатели артериол коры головного мозга при диабетической микроангиопатии и инфаркте мозга на ее фоне - Шаврин, В. А.; Авраменко, Ю. Н.; Шаврін, Володимир Олександрович; Авраменко, Юлія Миколаївна; Shavrin, V. O.; Avramenko, Yu. M. (My University, 2020)
Работа посвящена сравнительному анализу морфометрических показателей паренхиматозных артериол коры головного мозга при диабетической микроангиопатии и при ишемическом инфаркте головного мозга на фоне диабетической микроангиопатии, обусловленной сахарным диабетом 2 типа. Морфометрическое исследование микрососудов проведено на 60 секционных случаях смерти больных с сахарным диабетом 2 типа, с ишемическим полушарным инфарктом головного мозга на фоне диабета, а также группы условного контроля без церебральной сосудистой патологии. Выявлено, что при диабетической микроангиопатии и при церебральном ишемическом инфаркте на фоне сахарного диабета отмечается значительное увеличение толщины стенок артериол, увеличивается их наружный и внутренний диаметры, уменьшаются показатели внутреннего и наружного факторов формы, существенно увеличиваются индекс Вогенворта и индекс Керногана. При этом утолщение стенок микрососудов по сравнению с контролем значительно более выражено при ишемическом инфаркте головного мозга на фоне диабета. Увеличение индексов Вогенворта и Керногана по сравнению с группой условного контроля характерно для диабетической микроангиопатии, но значительно более резко выражено при церебральном инфаркте на фоне диабета, что соответствует более выраженному нарушению гемоциркуляции. Робота присвячена порівняльному аналізу морфометричних показників паренхіматозних артеріол кори головного мозку при діабетичній мікроангіопатії і при ішемічному інфаркті головного мозку на тлі діабетичної мікроангіопатії, зумовленої цукровим діабетом 2 типу. Морфометричне дослідження мікросудин проведено на 60 секційних випадках смерті хворих з цукровим діабетом 2 типу, з ішемічним півкульним інфарктом головного мозку на тлі діабету, а також групи умовного контролю без церебральної судинної патології. Виявлено, що при діабетичній мікроангіопатії і при церебральному ішемічному інфаркті на тлі цукрового діабету відзначається значне збільшення товщини стінок артеріол, збільшується їх зовнішній і внутрішній діаметри, зменшуються показники внутрішнього і зовнішнього факторів форми, істотно збільшуються індекс Вогенворта і індекс Керногана. При цьому потовщення стінок мікросудин в порівнянні з контролем значно більш виражене при ішемічному інфаркті головного мозку на тлі діабету. Збільшення індексів Вогенворта і Керногана в порівнянні з групою умовного контролю характерно для діабетичної мікроангіопатії, але значно більш різко виражене при церебральному інфаркті на тлі діабету, що відповідає більш значному порушенню гемоциркуляції. The mechanisms have adverse effects of diabetes on the vessels of the brain are not fully understood, and many questions remain related to the pathogenesis of cerebral infarction in patients with diabetes type 2. Purpose of the study. To determine the features of morphometric parameters of parenchymal microvessels (arterioles) of the cerebral cortex in diabetic microangiopathy and in ischemic cerebral infarction in diabetic microangiopathy due to diabetes mellitus type 2. The results of the study. Morphometric examination of microvessels was performed on 60 sectional cases of death of patients with type 2 diabetes, with ischemic hemispheric cerebral infarction in diabetes, and groups of conditional control without cerebral vascular pathology. The parameters were measured: a) external d1 and internal d2 diameter; b) external F1 and internal F2 form factors; c) area of the lumen; d) wall area. The formula was used: T = (d1-d2) / 2 for determining the thickness of the vascular wall. The Wogenworth index (iV) (the ratio of the wall area to the lumen area) and Kernogan index (iK) (the ratio of the wall thickness to the diameter of the vessel lumen) was calculated for estimating the functional state of the vessels. Thickening of the walls of microvessels is observed in diabetic microangiopathy. A significant increase in the thickness of the walls of arterioles is observed with ischemic cerebral infarction in diabetes – 1.8 times compared with the control and 1.3 times compared with the diabetes group. The outer diameter increases significantly and consistently from the control group (63.161 μm) to the groups with diabetes and brain infarction (68.785 μm and 77.82 μm, respectively). The inner diameter in the group with diabetes (44.695 μm) is almost unchanged compared with the control group (45.315 μm), in the group of cerebral infarctions increases to statistically significant value (48.99 μm). The Wogenworth and Kernogan indexes increase in the group with diabetes compared with the control group. An even greater increase in these indicators is observed in the group with brain infarction. Received data indicate a significant change in the function of the parenchymal microvessels of the brain in diabetic microangiopathy and ischemic infarction in patients with diabetes type 2. Conclusion. An increase in the wall thickness of the cerebral cortex arterioles is observed, their outer and inner diameters increase, the indices of the inner and outer form factors decrease, the Wogenworth index and the Kernogan index increase significantly compared with the control group in diabetic microangiopathy and in ischemic cerebral infarction of the brain with diabetes mellitus type 2.
Морфометричні показники артеріол кори головного мозку при діабетичній мікроангіопатії і інфаркті мозку на її тлі
Morphometric indicators of cerebral arterioles in diabetic microangiopathy and cerebral infarction in diabetes
Keywords: сахарный диабет; ишемический инфаркт; диабетическая микроангиопатия; морфометрия; цукровий діабет; ішемічний інфаркт; діабетична мікроангіопатія; морфометрія; diabetes mellitus; ischemic infarction; diabetic microangiopathy; morphometry